Magnetic resonance imaging in neurological disorders. Issue 9 (September 1990) - Elias-Jones, A C; Jaspan, T; Mellor, D H; Worthington, B S
Abstract : To investigate the role of magnetic resonance imaging (MRI) in neurological disorders, 115 children were studied in two groups. Group A (78 patients) was studied by paired computed tomography and MRI cranial scans. Group B (37 patients) was studied by paired computed tomography assisted myelography (CTM) and MRI spinal scans. In group A, the scans were generally equivalent for supratentorial tumours and for investigating fits, hydrocephalus, benign intracranial hypertension, and cerebral atrophies, but MRI scanning was superior for posterior fossa tumours and cysts. In group B, MRI scans were superior for intramedullary spinal tumours, spinal dysraphic problems with tethering or syrinx, and were complementary to CTM in diastematomyelia.